Reviews (Blackfriars, 1935)
Book reviewed in this article: A History of the Church. By Philip Hughes. The Teaching of History. By R. Worts. Christianity and the Nature of History. By H. G. Wood. Christliche Existenz. By Erich Przywara Peter and Veronica Growing Up. By Margaret Beech. Science And The Supernatural. A correspondence between Arnold Lunn and Professor J. B. S. Haldane Viscount Halifax. By J. G. Lockhart.